Can Type 1 Diabetes Be Prevented? Screening and Risk Assessment in Clinical Trials: A Narrative Review. - Tesla, Małgorzata; Gąska, Anna Agnieszka; Gutkowska, Marta; Jabłońska, Joanna; Wasik, Joanna; Armuła, Marta; Bongage, Claire; Piechowiak, Arkadiusz; Napieraj, Filip; Herc, Bartosz Przemysław (Quality in Sport, 2026)
Background. This review summarises recent clinical trials on type 1 diabetes (T1D) and emerging screening and prevention strategies. The increasing incidence of T1D raises interest in early detection and potential prevention. Ongoing studies focus on newborn risk assessment, islet autoantibody screening and preventive strategies. Aim. This review aims to present current knowledge on T1D prevention, screening methods for risk assessment and identification of preclinical disease, and to highlight recent directions in clinical research. Material and methods. A literature search was conducted in PubMed, Scopus and Google Scholar. Retrospective and cohort studies, literature reviews, systematic reviews, guidelines, clinical trial protocols and randomised controlled trials were included. The following keywords were used: ‘type 1 diabetes’, ‘risk factors’, ‘ketoacidosis’, ‘screening’, ‘newborn screening’, ‘genetic risk’, ‘prevention’, ‘preclinical stage’. The search focused on recent clinical trials. Results. Clinical studies demonstrate a shift towards earlier detection of T1D through screening strategies combining genetic risk assessment with islet autoantibody testing. These strategies allow identification of at-risk individuals and long-term monitoring. Studies confirm that detection of preclinical stages is associated with reduced incidence of diabetic ketoacidosis at diagnosis and a milder disease course. Early diagnosis enables access to disease-modifying therapy with teplizumab, which can delay disease progression. Preventive approaches, including oral insulin immunotherapy and microbiome-targeted interventions, are under investigation, with mixed results. Conclusions. T1D can be identified at earlier stages using combined genetic and immunological screening strategies, improving clinical outcomes at diagnosis. However, effective prevention remains limited. Further research is required to optimise screening and its implementation in clinical practice.